Projekt Network for Tuning Standards and Quality of Education programmes for Speach and Language Therapists in Europe – cel i założenia) - Przybyla, Olga (Logopedia Silesiana, 2012)
Project Network for Tuning Standards and Quality of Education programmes for Speech and Language Therapists in Europe – the purpose and assumptions ...